Electrospun PCL Nerve Wrap Coated with Graphene Oxide Supports Axonal Growth in a Rat Sciatic Nerve Injury Model - Meaghan E. Harley-Troxell; Richard Steiner; Steven D. Newby; Austin J. Bow; Thomas J. Masi; Nicholas Millis; Alicia Adina Matavosian; Dustin Crouch; Stacy Stephenson; David E. Anderson; Madhu Dhar (MDPI AG, 2024)
Background/Objectives: Peripheral nerve injuries (PNIs) are a debilitating problem, resulting in diminished quality of life due to the continued presence of both chronic and acute pain. The current standard of practice for the repair of PNIs larger than 10 mm is the use of autologous nerve grafts. Autologous nerve grafts have limitations that often result in outcomes that are not sufficient to remove motor and sensory impairments. Bio-mimetic nanocomposite scaffolds combined with mesenchymal stem cells (MSCs) represent a promising approach for PNIs. In this study, we investigated the potential of an electrospun wrap of polycaprolactone (PCL) + graphene oxide (GO), with and without xenogeneic human adipose tissue-derived MSCs (hADMSCs) to use as a platform for neural tissue engineering. Methods: We evaluated, in vitro and in vivo, the potential of the nerve wrap in providing support for axonal growth. To establish the rat sciatic nerve defect model, a 10 mm long limiting defect was created in the rat sciatic nerve of 18 Lewis rats. Rats treated with the nanocomposites were compared with autograft-treated defects. Gait, histological, and muscle analyses were performed after sacrifice at 12 weeks post-surgery. Results: Our findings demonstrate that hADMSCs had the potential to transdifferentiate into neural lineage and that the nanocomposite successfully delivered hADMSCs to the injury site. Histologically, we show that the PCL + GO nanocomposite with hADMSCs is comparable to the autologous nerve graft, to support and guide axonal growth. Conclusions: The novel PCL + GO nerve wrap and hADMSCs used in this study provide a foundation on which to build upon and generate future strategies for PNI repair.